Ecological redline policy may significantly alter urban expansion and affect surface runoff in the Beijing-Tianjin-Hebei megaregion of China. (12th October 2020) - Ju, Xinhui; Li, Weifeng; He, Liang; Li, Junran; Han, Lijian; Mao, Jingqiao
Abstract: Urban expansion leads to surface changes that disrupt hydrological processes and increases flooding risks in cities. This increase may be severe in urban megaregions where clusters of cites have agglomerated. The China Ecological Redline Policy (ERP) is a national policy that protects priority areas with high-value ecosystem services. However, it is not clear how the ERP alters megaregion expansion and what this means for surface runoff across entire regions. By integrating specified models, we developed future urban expansion scenarios for 2030 with and without the ERP in the Chinese Beijing-Tianjin-Hebei (BTH) megaregion. The annual surface runoff volume under the ERP scenario decreased by 78 million m 3 compared to the non-ERP involved scenario, but the ERP effectiveness at surface runoff regulation was different between the ecological redline areas (ERAs) and the non-ERAs. This suggested that multi-solutions should be incorporated into megaregions, such as regional ERPs and local, nature-based solutions, which could efficiently reduce the risk of urban flooding across whole regions.